Jan Paweł II jako postać epizodyczna w filmach fabularnych. Rekonesans wstępny = John Paul II and his secondary and cameo roles in feature films. A preliminary reconnaiss ance - Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
John Paul II entered popular culture. Like any other pope, he appeared in movies as the main, but also as a secondary character, a motif shown in a film for a fraction of a second. This article is precisely about this phenomenon, about his cameo roles, about different fragments of archival documents, photos and portraits of the Pope, as well as allusions to the Holy Father that are interwoven into feature films.
Keywords: Jan Paweł II, papież (1929-2005); film fabularny